Refrigeration and air conditioning technology, 3rd edition : - Whitman, William C. (Delmar, 1995)
This edition offers an authoritative overview of all types of refrigeration and air conditioning systems! The new full- color edition covers virtually every type of system from gas, to oil, to electric, to large-scale commercial systems.